2008
DOI: 10.1038/ejhg.2008.11
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity mapping in a family presenting with schizophrenia, epilepsy and hearing impairment

Abstract: Homozygosity mapping within consanguineous families is a powerful method of localising genes for autosomal recessive disease. We investigated a family from Punjab, Pakistan, a region where consanguineous marriages are frequent. The parents have no detectable clinical disorders. However, five out of six children present with schizophrenia, epilepsy or hearing impairment either alone or in combination. This unusual phenotype in several offspring of first cousins is strongly suggestive of a rare, Mendelian recess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…The idea that long homozygous by descent regions may harbor disease-causing genes (particularly recessive alleles) has been explored in several studies, including patients with autism (18), Alzheimer’s disease (17), Parkinson’s disease (19), schizophrenia (20), and bipolar affective disorder (21). When our group examined the germ-line SNP array data of 74 colorectal cancer patients, we found that the percentage of those having autozygous segments greater or equal to 4 Mb is at least twice as high as control groups (22).…”
Section: Autozygous Segments: Are They Useful In Genetic Studies Of Dmentioning
confidence: 99%
“…The idea that long homozygous by descent regions may harbor disease-causing genes (particularly recessive alleles) has been explored in several studies, including patients with autism (18), Alzheimer’s disease (17), Parkinson’s disease (19), schizophrenia (20), and bipolar affective disorder (21). When our group examined the germ-line SNP array data of 74 colorectal cancer patients, we found that the percentage of those having autozygous segments greater or equal to 4 Mb is at least twice as high as control groups (22).…”
Section: Autozygous Segments: Are They Useful In Genetic Studies Of Dmentioning
confidence: 99%
“…Detailed behavioral analyses for other auxiliary subunits have not been performed yet. In this context, it is worth mentioning that genetic analyses (linkage analyses) suggested that TARP Îł-2 and 3 might be implicated in diseases of the central nervous system such as familial epilepsy, schizophrenia, and bipolar disorders [97][98][99][100][101]. …”
Section: Discussionmentioning
confidence: 99%
“…It has also been widely hypothesized that the disturbances in auditory processing occur frequently in schizophrenic patients compared with normal subjects5859. Although controversy exists in the association between sensory inputs and schizophrenia, there are a number of clinical and genetic studies reporting a contribution of hearing impairment to psychiatric disorders596061, implying the significant influence of auditory stimuli in neurodevelopmental processes. Given that mutations in the Tara locus are associated with deafness4243, it is noteworthy that there is a high comorbidity between hearing defects and psychiatric disorders such as schizophrenia in the general population58596061.…”
Section: Discussionmentioning
confidence: 99%